2014
DOI: 10.3109/2000656x.2014.964726
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells show promising results for lymphoedema treatment – A literature review

Abstract: Lymphoedema is a debilitating condition, manifesting in excess lymphatic fluid and swelling of subcutaneous tissues. Lymphoedema is as of yet still an incurable condition and current treatment modalities are not satisfactory. The capacity of mesenchymal stem cells to promote angiogenesis, secrete growth factors, regulate the inflammatory process, and differentiate into multiple cell types make them a potential ideal therapy for lymphoedema. Adipose tissue is the richest and most accessible source of mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…While several microsurgical techniques have been presented over the last decades, they continue to be somewhat experimental due to the lack of clear evidence and therefore conservative management remains the standard of care. Preclinical and sparse clinical studies have suggested that cell therapy using autologous mesenchymal stromal cells from various sources including adipose tissue, muscle, and bone marrow can alleviate lymphedema [2]. The two studies performed so far in humans have been with cells derived from bone marrow [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…While several microsurgical techniques have been presented over the last decades, they continue to be somewhat experimental due to the lack of clear evidence and therefore conservative management remains the standard of care. Preclinical and sparse clinical studies have suggested that cell therapy using autologous mesenchymal stromal cells from various sources including adipose tissue, muscle, and bone marrow can alleviate lymphedema [2]. The two studies performed so far in humans have been with cells derived from bone marrow [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The cells from adipose tissue can be used for therapeutic purposes, either freshly isolated as the stromal vascular fraction (SVF, also called adipose‐derived regenerative cells [ADRC]), or culture‐expanded as the adipose‐derived stem cells (ASC). Adipose‐derived cell therapy has shown potential in almost every preclinical animal model and the time is ripe for clinical translation of this potential.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, stem/progenitor cells with, albeit limited, capacity to differentiate down the lymphatic endothelial cell lineage were found in cord/peripheral blood 21 25 and bone marrow/adipose tissue (stroma) 22 , 23 , 25 31 . Multiple cell types have been tested in various animal models to evaluate their efficacy for lymphatic regeneration, including mesenchymal stem cells (reviewed in refs 32 , 33 ), adipose tissue stem cells 31 , 32 , 34 , 35 , pluripotent stem cells 3 and bone marrow-derived endothelial cell precursors 27 . However, no studies have provided evidence for their therapeutic potential to support restoration of the lymphatic vasculature from the capillary to the collector level, which is a prerequisite for effective lymphedema treatment 9 .…”
Section: Introductionmentioning
confidence: 99%